THE UNIVERSITY AND ITS ROLE IN THE HUMAN RESOURCES TRAINING TO ACT WITH DISABLE PEOPLE IN THE ADAPTED SPORT AREA - Brancatti, Paulo Roberto [UNESP] (Inst Fed Education, Science & Technology Of Goias, Campus Inhumas, 2018)
This article has as objective to present and describe several pedagogical actions that are developed in UNESP/FCT-Presidente Prudente Physical Education Course with regard to Physical Education professional training issues to work with disable people in adapted sport area, whether it's in the initial phase or in the continuity phase in studies and researches in this area. For this, we present in a demonstrative chart the subjects, projects and pedagogical actions compositions regarding the teacher training in Physical Education. And in text development we present some theoretical studies in the area of Education, Physical Education and Adapted Physical Education, that are in agree to several authors that emphasize that APE is growing in the country and that formative actions of Higher Institutions strengthen the current moment, together with the area of Education. And as results, we present in text completion, reports from the ones who acted in some projects during student period and how they demonstrate this in the process of academic formation and in the experience gained from these pedagogical actions.
Keywords: training; sports; disable people